THE IMPACT OF USING AI-BASED LANGUAGE LEARNING PLATFORMS ON ENGLISH SPEAKING SKILLS OF COLLEGE STUDENTS - Cahyono, Agus Eko; Rosita, Ria (TRANSFORMATIONAL LANGUAGE, LITERATURE, AND TECHNOLOGY OVERVIEW IN LEARNING, 2023)
The integration of artificial intelligence (AI) in language learning has created new opportunities to enhance the quality and personalization of educational experiences. This study aims to explore the impact of using AI-based language learning platforms on the English-speaking skills of college students. The research employs a quasi-experimental design with two groups: a control class using conventional learning methods and an experimental class using AI-based learning platforms. The research population consists of students from University X, with a sample of 32 students in the experimental class and 34 students in the control class. Data were collected through pre-tests, treatment, and post-tests. The results indicate a significant improvement in English speaking skills in the experimental group compared to the control group. Data analysis shows that AI-based learning platforms are effective in enhancing speaking skills, particularly due to the interactive features and adaptive feedback provided by the platforms. These findings suggest that the use of AI technology in language learning can yield better results compared to traditional methods, supporting further integration of this technology in language education.